PEMBERIAN REMISI TERHADAP NARAPIDANA DITINJAU DARI PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR 16 TAHUN 2023 DI LEMBAGA PEMASYARAKATAN KELAS III TELUKDALAM - Waruwu, Refisi (JURNAL PANAH KEADILAN, 2025)
Remission is a reduction in the period of serving a sentence given to prisoners and children who are in conflict with the law. A convict is a person who is serving a prison sentence. The definition of prisoner according to the Indonesian dictionary is a convicted person (a person who is serving a sentence for committing a criminal act). The aim of this research is to find out how the granting of remissions to convicts is seen from the Regulation of the Minister of Law and Human Rights Number 16 of 2023 at the Class III Telukdalam Penitentiary. The type of research used is sociological legal research, namely examining applicable legal provisions based on existing facts in a society. Data collection was carried out using primary data, secondary data and tertiary data. obtained from secondary legal materials. The data analysis used is qualitative data analysis. Qualitative data analysis is carried out together with the data collection process. Based on the research findings and discussion in the research, the granting of remissions to prisoners is viewed from the Minister of Law and Human Rights Regulation Number 16 of 2023. At the Class III Telukdalam Penitentiary, remissions are always granted to prisoners who have fulfilled the requirements set out in the provisions of the law. -invitation. Based on the results of the conclusions that have been made by the researcher, the researcher provides suggestions regarding the granting of remissions to prisoners in view of the Minister of Law and Human Rights Regulation Number 16 of 2023 at the Class III Telukdalam Penitentiary, namely that the granting of remissions to prisoners continues to be carried out to fulfill the prisoners' rights.